Legal and regulatory frameworks for urbanisation and urban planning and management in Nigeria (2017)
Urban environmental problems are of different dimensions and are mostly due to geologic, climatic and cultural factors. The thrust of this paper is to examine the legal and regulatory frameworks for urbanisation, urban planning and management in Nigeria. The paper argues that cultural factors seem to be more pronounced in the Nigerian context because most of the identified urban environmental issues are so much associated with the way of life of the people either as reactions to urbanisation or their spatial heritage. The paper observes that Nigeria never lacks good policies, legislation and institutional frameworks, but good implementation have always been the bane. The papers submits that the failure of existing laws and regulations to make significant impact in protecting and preserving the environment are due to poor implementation, deficient legislations, lack of political will, poor funding and lack of adequate manpower. The paper therefore recommends amendment of the existing legislations on urban planning and management to introduce stiffer penalty for offender and violator of Nigerian Urban and Development Act. It further proposes that all legal ambiguity, lack of qualified personnel, inadequate funding should be addressed while a more coherent and consistent Land Use Policy should be formulated by the government to take into cognisance the needs of the environment without necessarily hampering economic growth ami development. In similar vein, the judiciary' should be proactive in giving relevance to policy considerations in reaching their decisions and not relegating policies completely and ineffective.